2002
DOI: 10.1074/jbc.m204852200
|View full text |Cite
|
Sign up to set email alerts
|

Active Site Contribution to Specificity of the Aspartic Proteases Plasmepsins I and II

Abstract: Plasmepsins I and II (PM I and II) are aspartic proteases involved in the initial steps of Plasmodium hemoglobin degradation. They are attractive targets for antimalarial drug development. The two enzymes are 73% identical, yet have different substrate and inhibitor specificities. The x-ray structures of proform and mature PM II have been determined, but models of PM I do not adequately explain the selectivity of the two proteases. To better understand the basis of these recognition differences, we have identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
3
19
0
Order By: Relevance
“…Analyses of substrate preferences by Siripurkpong et al 104 showed an increased preference of Plm I for serine in the P1 0 position, whereas Plm II preferred leucine and methionine in this position. We also found that changes in the P1 0 position of basic hydroxyethylamine inhibitors, related to inhibitors 20-24, resulted in different Plm I/II selectivities, indicating the S1 0 subsite to be significantly different in the two plasmepsins.…”
Section: Hydroxyethylaminesmentioning
confidence: 97%
See 1 more Smart Citation
“…Analyses of substrate preferences by Siripurkpong et al 104 showed an increased preference of Plm I for serine in the P1 0 position, whereas Plm II preferred leucine and methionine in this position. We also found that changes in the P1 0 position of basic hydroxyethylamine inhibitors, related to inhibitors 20-24, resulted in different Plm I/II selectivities, indicating the S1 0 subsite to be significantly different in the two plasmepsins.…”
Section: Hydroxyethylaminesmentioning
confidence: 97%
“…104 Hence, it is evident that remote amino acids from the active site probably play important roles in substrate and inhibitor binding, possibly by inducing different conformations of the active site. To examine which of the plasmepsins, I or II, is most important in parasite growth, several Plm I-and II-selective inhibitors have been assessed in erythrocyte-based assays.…”
Section: B Plasmepsin I Inhibitorsmentioning
confidence: 99%
“…The preferences at the primed positions have been characterized in detail with a random decamer peptide library, and it was shown that Leu and Ser are preferred at P1Ј and P2Ј, respectively, whereas there was little specificity at other positions (30). The availability of related sequences has been beneficial to elucidate the substrate specificity of PM II.…”
Section: Discussionmentioning
confidence: 99%
“…Although plasmepsins from each of the four species have been cloned and expressed as recombinant enzymes (12,18,22,44,45), there is still very little known about many of the peptidases recently discovered from the P. falciparum genome-sequencing project (46). The most fully characterized plasmepsin is PfPM2, where numerous structures (18)(19)(20) and kinetic studies (21,31,45,47) have aided in identifying the determinants of substrate specificity.…”
Section: Discussionmentioning
confidence: 99%